Journal of the Institution of Engineering ( India ) 1.Civil Engineering 2.Computer Enginering 3.Chemical Engineering (IEI, 2008)
Volume No.89-92 [ 2008-11 ] Issue No.13 Issues [ 1.Civil Engineering ] Volume No.89-92 [ 2008-11 ] Issue No.6 Issues [ 2.Computer Engineering ] Volume No.89-92 [ 2008-11 ] Issue No.5 Issues [ 3.Chemical Engineering ]